EPIDERMAL GROWTH FACTOR RECEPTOR EXPRESSION IN NON-KERATINIZED NASOPHARYNGEAL CARCINOMA SUBTYPE AT PADANG - Histawara Subroto; Sukri Rahman; Bestari J Budiman; Aswiyanti Asri; Hafni Bachtiar (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Introduction: Patients with nasopharyngeal carcinoma have a poor prognosis, there are several factors that cause it to happen, one of the existing therapeutic response has been inadequate. Expression of Epidermal Growth Factor Receptor (EGFR) has been used as a biological marker targeted therapy in nasopharyngeal carcinoma. Histopathologic subtype tumors also determine the prognosis of patients with nasopharyngeal carcinoma. Objective: The aim of the study to determine between the expression of epidermal growth factor receptor between non-keratinized differentiated and undifferentiated subtypes in nasopharyngeal carcinoma and correlation with their clinical stage. Study design, Cross-sectional comparative study. Place and duration study, Department of Otorhinolaryngology, Department of Pathology Anatomy in Dr. M. Djamil Hospital, Padang and Department of Pathology Anatomy in Gajah Mada University, between May 2015 until October 2015 Material and methods: We included 36 samples paraffin blocks of nasopharyngeal carcinoma biopsy, respectively 18 paraffin blocks are non-keratinized differentiated and 18 non-keratinized undifferentiated nasopharyngeal carcinoma subtypes. Each sample examined EGFR expression by immunohistochemical staining methods. Results: There were positive EGFR expression results in all sample as 69.4%. Expression of EGFR positive non-keratinized differentiated subtypes in nasopharyngeal carcinoma as 77.8% and undifferentiated subtype as 61.6%. There are no significant differences of EGFR expression between non keratinized differentiated and undifferentiated subtypes nasopharyngeal carcinoma (P>0.05). There are no significant differences of EGFR expression between new and advanced stage nasopharyngeal carcinoma (P>0.05). Conclusion: There were no significant differences of EGFR expression between non-keratinized differentiated and non-keratinized undifferentiated subtypes in nasopharyngeal carcinoma. Analysis of the study also showed no significant differences of EGFR expression based on the clinical stage nasopharyngeal carcinoma.